(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Physical education and sports has been widely accepted as an integral part of the total education process. There is a growing realization among the educationists that in teaching, physical education should be an educational objective of priority. Introduction of physical education and sports as a compulsory subject in education institutions is today‟s demand. Physical education and sports play an important role in day to day life of different people in different ways. Sports serve as fertile ground for the growth and successful development of relations among different people of different nations. Physical education and sports play an important role in day to day life of different people in different ways. Sports serve as fertile ground for the growth and successful development of relations among different people of different nations. Sports consist of two types of events i.e. team events and individual events. Athletes choose either team event or individual event which depends upon various factors such as psychological, economic and physical and personality etc. All these factors influence the athlete to choose the suitable event because; in sports an athlete has to encounter numerous predictable and unpredictable situations. His physical, tactical, technical, sociological, psychological powers help him to adapt a particular situation. Many scholars in the recent past have studied the social and psychological makeup of athletes of team and individual events. Their findings can be understood better, if we try to understand the event‟s role and situation of specific socio psychological interaction of each athlete. Physical education trends have developed recently to incorporate a greater variety of activities. Introducing students to activities like bowling, walking/hiking, or Frisbee at an early age can help students develop good activity habits that will carry over into adulthood. Some teachers have even begun to incorporate stress reduction techniques such as yoga and deepbreathing. Teaching non-traditional sports to students may also provide the necessary motivation for students to increase their activity, and can help students learn about different cultures. For example, while teaching a unit about lacrosse (in, say, Arizona, USA), students can also learn a little bit about the Native American cultures of the Northeast and Eastern Canada, where lacrosse originated. Teaching non-traditional (or nonnative) sports provides a great opportunity to integrate academic concepts from other subjects as well (social studies from the example above), which may now be required of many P.E. teachers. There are four aspects of P.E. which is physical, mental, social, and emotional. Another trend is the incorporation of Health and Nutrition to the physical education curriculum. The Child Nutrition and WIC Re-authorization Act of 2004 required that all school districts with a federally funded school meal program develop wellness policies that address nutrition and physical activity. While teaching students sports and movement skills, P.E. teachers are now incorporating short health and nutrition lessons into the curriculum. This is more prevalent at the elementary school level, where students do not have a specific Health class. Recently most elementary schools have specific health classes for students as well as physical education class. With the recent outbreaks of diseases such as swine flu, school districts are making it mandatory for students to learn about practicing good hygiene along with other health topics. Today many states require Physical Education teachers to be certified to teach Health courses. Many colleges and Universities offer both Physical Education and Health as one certification. This push towards Health education is beginning in the intermediate level, including lessons on bullying, self-esteem and stress and anger management. Steps of the proposed research.